THE COUNTER-ATTACK IN FUTSAL: OBSERVATION AND ANALYSIS OF THE GAME OF THE MINEIRA SUB-15 TEAM IN THE BRAZILIAN TEAMS CHAMPIONSHIP (Fiep Bulletin - online, 2015)
The researches related to the collective sport games have been increasing in the last few years as well as the studies related to the game analysis and observation. Trainings have been produced from this process and the level of the matches in different events, have been gradually increased. Classified as a collective sport game, futsal is an event which present four distinct fases, defense, attack, counter-attack and defensive return, the two last considering transition moments. The present study analyzed the offensive actions of the Mineira sub-15 Team in the Brazilian Teams Championship 2005 with emphasis in counter-attacks, checking the effectiveness, functional used structures (numerical inferiority, equality and superiority), and the time spent in the execution. It was noticed that most of the conclusions performed happened in Organized Game situations (37,6%) followed by the stopped balls (28,7%) and by the counter-attacks showed a higher effectiveness of conclusion (30,5%) proving that way, the importance of this action. The counter-attacks happened most of the cases in the numerical structures of equality and superiority and the situations of numerical superiority represented a higher effectiveness of conclusion, 40%. At last, it was verified that the counter-attacks were performed in an average time of 4,93 seconds, proving this way the speed of this action. It is suggested that in future studies, all the offensive actions be analyzed including the ones which did not generate conclusions and that these actions may be analyzed in courts with different sizes to link the offensive actions to the court dimensions and his consequences for the game.
Keywords: game analysis and observation; counter-attack; futsal.